2013
DOI: 10.1038/cddis.2013.188
|View full text |Cite
|
Sign up to set email alerts
|

Eleostearic acid induces RIP1-mediated atypical apoptosis in a kinase-independent manner via ERK phosphorylation, ROS generation and mitochondrial dysfunction

Abstract: RIP1 is a serine/threonine kinase, which is involved in apoptosis and necroptosis. In apoptosis, caspase-8 and FADD have an important role. On the other hand, RIP3 is a key molecule in necroptosis. Recently, we reported that eleostearic acid (ESA) elicits caspase-3- and PARP-1-independent cell death, although ESA-treated cells mediate typical apoptotic morphology such as chromatin condensation, plasma membrane blebbing and apoptotic body formation. The activation of caspases, Bax and PARP-1, the cleavage of AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Prior to its identification as a necroptosis-inducer, ESA was shown to reduce growth of a human colon cancer in mice [28,29]. Another report showed that ESA induces RIPK1-mediated necroptosis of tumor cells via generation of ROS and ATP reduction without detectable effects on normal cells [27]. Our finding that ESA induced necroptosis in OVSAHO cells (Fig.…”
Section: α-Eleostearic Acid Reduces Survival Of Transformed Fte and Hsupporting
confidence: 54%
See 1 more Smart Citation
“…Prior to its identification as a necroptosis-inducer, ESA was shown to reduce growth of a human colon cancer in mice [28,29]. Another report showed that ESA induces RIPK1-mediated necroptosis of tumor cells via generation of ROS and ATP reduction without detectable effects on normal cells [27]. Our finding that ESA induced necroptosis in OVSAHO cells (Fig.…”
Section: α-Eleostearic Acid Reduces Survival Of Transformed Fte and Hsupporting
confidence: 54%
“…We chose to test induction of necroptosis in OVSAHO cells using P4, TNFα, or (9Z,11E,13E)-octadecatrienoic acid, also known as α-eleostearic acid or ESA. ESA has been demonstrated to induce necroptosis in tumor cells [27] and reduce human colon cancer growth in mice [28,29]. OVSAHO cells are PGR positive, TP53-mutant, have a homozygous BRCA2 deletion, and are considered highly-representative of HGSOC tumors [30].…”
Section: Established Hgsoc Cells Maintain the Capacity To Activate Nementioning
confidence: 99%
“…The following validated siRNAs were used for rat AIF and Atg5 knockdown, respectively [10, 11]. siAIF: 5’-cauagaagcaugcagcaucuccugc-3’; siAtg5: 5’-gguuuggacgaauuccaacuuguuu-3’.…”
Section: Methodsmentioning
confidence: 99%
“…2) [85]. Finally, RIP1 was recently reported to be involved in eleostearic acid-induced atypical apoptosis by promoting reactive oxygen species (ROS) production [86]. …”
Section: Non-necrotic Function Of Rip1 In Apoptosis and Inflammatomentioning
confidence: 99%